(untitled) (Research, Society and Development, 2022)
In order to have the maximum quality of life and comfort, several factors need to be met. One of the main points to consider is housing, having a well-planned building avoids problems in the most diverse ways for the owner and maximizes urban well-being in the region, with the objective of generating a better quality of life for the users of the space. The present article deals with a study of a single-family residence with two floors, built in the EPS type construction system, located in the city of Recife-PE, focusing on the evaluation of possible occurrences of pathological manifestations, as well as presenting the results of the entire project. process. As a methodology, a case study was used, based on the IBAPE National Property Inspection standard. The criterion used was based on the Risk Analysis associated with environmental use and exposure. In the course of the article, the problems identified in the building were exposed, in which several problems of cracking, deformation of plate elements, electrical problems and infiltration were found. In addition, there is the absence of a technical project, possible execution problems and the lack of a specialized person in charge to accompany the work, to ensure greater safety throughout the process.